Myosin Va: Capturing cAMP for synaptic plasticity - Rudolf, Rüdiger (Frontiers in Physiology, 2024)
The plus-end directed actin-dependent motor protein, myosin Va, is of particular relevance for outward vesicular protein trafficking and for restraining specific cargo vesicles within the actin cortex. The latter is a preferred site of cAMP production, and the specificity of cAMP signaling is largely mediated through the formation of microdomains that spatially couple localized metabotropic receptor activity and cAMP production to selected effectors and downstream targets. This review summarizes the core literature on the role of myosin Va for the creation of such a cAMP microdomain at the mammalian nerve-muscle synapse that serves the activity-dependent recycling of nicotinic acetylcholine receptors (nAChR), a principal ligand-gated ion channel which is imperative for voluntary muscle contraction. It is discussed that (i) the nerve-muscle synapse is a site with a unique actin-dependent microstructure, (ii) myosin Va and protein kinase A regulatory subunit Ialpha as well as nAChR and its constitutive binding partner, rapsyn, colocalize in endocytic/recycling vesicles near the postsynaptic membrane, and (iii) impairment of myosin Va or displacement of protein kinase A regulatory subunit Ialpha lead to loss of nAChR stability. Regulation of this signaling process and underlying basic pieces of machinery were covered in previous articles, to which the present review refers.